434 DEMOGRAPHIC DETERMINANTS OF URINARY CALCIUM EXCRETION IN HEALTHY CHILDREN. Issue 1 (1st January 2007) - Butani, L.; Wegelin, J. A.; Byrd, R. S.
Abstract : Elevated urinary calcium excretion is a risk factor for renal calculi. Age-related differences in calcium excretion have been shown in Caucasian children; few data are present for other ethnicities. Our study aimed to establish normative data for calcium excretion in children of different ethnicities by age. A convenience sample of 1, 365 healthy children (3-18 years) was prospectively recruited from August 2002 to June 2005. The random urinary calcium to creatinine ratio (ratio) was used to measure calcium excretion. Quantile regression was used to assess the relationship between age and the ratio. Of the subjects, 558 (31%) were Caucasian, 393 (22%) were African American, 272 (15%) were Hispanic, and 142 (8%) were Asian. The 95th percentiles for the ratio are shown in Table 1 for a subset of the study sample. Compared with Caucasians, only African Americans had a lower ratio ( p < .001). The ratio decreased with age, but only among Caucasians and African Americans ( p < .05). In conclusion, significant ethnic differences exist in urinary calcium excretion, with Caucasians having the highest and African Americans the lowest ratio. Follow-up of children at different levels of calcium excretion is under way to determine the predictive value of the ratio for development of calculi.